Workers' Remittances : An Overlooked Channel of International Business Cycle Transmission? - Barajas, Adolfo (IMF Working Papers; Working Paper, 2012)
This paper shows that remittance flows significantly increase the business cycle synchronization between remittance-recipient countries and the rest of the world. Using both aggregate and bilateral remittances data in a panel data setting, the study demonstrates that this effect is robust and causal. Moreover, the econometric analysis reveals that remittance flows are more effective in channeling economic downturns than upswings from the sending countries to remittance-receiving economies. The analysis suggests that measures of openness and spillovers could be enhanced by accounting for the role of the remittances channel.